Lectures on quantum mechanics : Fundamentals and applications - Pathak, Anirban; Ghatak, Ajoy (Delhi : Viva Book, 2019)
The book primarily aims to elucidate various concepts of quantum mechanics and provides an exposure to modern applications of quantum mechanics ranging from the use of squeezed states in the detection of gravitational waves (in the famous LlGO experiment) to quantum computers placed in the cloud. It also aims to make teaching of quantum mechanics interesting by providing a clear prescription for performing quantum-mechanical experiments in the classroom by using a cloud-based quantum computer. Such a prescription had never been provided earlier. Making it more exciting and complete, a lucid description of the historical development of quantum mechanics is provided along with the conceptually clearer mathematical and physical description of the textbook type standard problems of quantum mechanics. Further, issues associated with the foundations of quantum mechanics are also discussed in the chapter dedicated to the Aharonov-Bohm effect.
Keywords: Quantum theory; Quantum mechanics; Physics; Mathematical physics